Формування ергономічної компетентності магістрантів спеціальності "Педагогіка вищої школи" на міждисциплінарній основі - Демідова, Юлія Євгенівна; Ігнатюк, Ольга Анатоліївна (Класичний приватний університет, 2015)
У статті розглянуто сутність ергономічної компетентності, її важливості для суб’єктів освітнього процесу і практичних кроків, які визначатимуть ефективність процесу її формування у слухачів магістерської програми спеціальності “Педагогіка вищої школи” на міждисциплінарній основі ергономічних та психолого-педагогічних дисциплін. Визначено, що ергономічна компетентність формується на основі сукупності соціально-психологічних, фізіологічних, психологічних, психофізіологічних, антропометричних та гігієнічних складових. Проаналізовано завдання курсів інтегрованих ергономічних та психолого-педагогічних дисциплін у системі підготовки майбутніх викладачів.

The article focuses on clarifying the nature of ergonomic competence, its importance to the subjects of the educational process and the practical steps that will determine the effectiveness of the process of its formation in the master’s program student’s specialty “Pedagogy of Higher Education” on an interdisciplinary basis of ergonomic and psychopedagogical disciplines. In the article noted that the analysis of research indicates an increase in attention to the consideration of ergonomic problems in the education system. It is concluded that the purpose of ergonomic disciplines is to improve professional activities, preservation of health (security), personal development (comfort, satisfaction with the content, forms, results of operations). The article deals with the problem of integrated courses ergonomic and psychopedagogical disciplines in the training of future teachers who are to develop their abilities to adapt quickly to new social factors associated with changes in the occupational structure of the workspace, production processes, computerization of production, increasing stressful situations, increase the level of injury. Complex methodological competence ergonomic components are formed on the basis of group components, which represent a set of sociopsychological, physiological, psychological and psycho-physiological, anthropometric and hygiene. In the article determined that important knowledge than individual features of perception, thinking and actions of the working person, and research activities as a whole in the calculation of all the circumstances that affect the success of human activity.
Formation of Competence Ergonomic Undergraduates Specialty “Pedagogy of Higher Education” on an Interdisciplinary Basis
Keywords: підготовка професійна; підготовка фахівців; підготовка кадрів; діяльність професійна; викладач; ергономіка; ergonomic discipline; ergonomic competence; teacher; training; professional activity